2019
DOI: 10.1103/physrevfluids.4.034201
|View full text |Cite
|
Sign up to set email alerts
|

Steady flow regimes and mixing performance in arrow-shaped micro-mixers

Abstract: The different flow regimes occurring for increasing Reynolds number (Re) in a arrow-shaped micro-mixer operated for liquid mixing are investigated by the synergic use of experimental flow visualizations and direct numerical simulations. The tilting angle of the arrow-mixer inlet channels with respect to those of the T-shaped mixer is α = 20 • . Consistently with previous studies in the literature, it is found that the onset of the engulfment regime, and consequently the sharp increase of the degree of mixing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…The anticipation of the engulfment regime onset was found to become more pronounced by increasing the tilting angle α. However, confirming the clues in the work of Galletti et al, 26 a significant drop of mixing was observed within the steady engulfment regime for α larger than some critical value (between 15 ○ and 20 ○ for the configuration investigated in the work of Mariotti et al 27 ). This is not present for T-mixers and low tilting angles.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…The anticipation of the engulfment regime onset was found to become more pronounced by increasing the tilting angle α. However, confirming the clues in the work of Galletti et al, 26 a significant drop of mixing was observed within the steady engulfment regime for α larger than some critical value (between 15 ○ and 20 ○ for the configuration investigated in the work of Mariotti et al 27 ). This is not present for T-mixers and low tilting angles.…”
Section: Introductionsupporting
confidence: 83%
“…The anticipation of the engulfment onset in arrow-shaped mixers is confirmed by the simulations in the work of You et al 22 On the other hand, in the numerical simulations of Galletti et al, 26 a non-monotonic behavior of the degree of mixing with Re was found in arrow-shaped mixers within the engulfment regime, which is conversely not observed for T-mixers. In a recently published paper, 27 a systematic investigation on the steady regimes occurring in arrow-shaped micro-mixers fed by liquids and with varying the tilting angle α was carried out. Experimental flow visualizations and numerical simulations were used together to study mixers having square inlet sections and a rectangular 2:1 outlet.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the first strategy, arrow-shaped junctions, in which the axis of the inlet channels is tilted downward with respect to the mixing channel, allow us to achieve the onset of the engulfment regime at significantly lower Reynolds numbers compared to T-mixers. However, the mixing performance does not monotonically increase with Reynolds [45]. On the contrary, the onset of the engulfment regime occurs at a larger Reynolds number if Y-shaped junctions are used and, thus, this device appears to be less efficient in mixing [46][47][48].…”
Section: Introductionmentioning
confidence: 99%